Aktivitas Antifeedant dan Antioviposisi Ekstrak Daun Tithonia terhadap Kutu Kebul - Dian Susanti; Rahma Widyastuti; Ato Sulistyo (Universitas Sebelas Maret, 2015)
The increasing demand of jamu/traditional medicine was followed by the demands of raw materials quality based on Good Agricultural and Collection Practices (GACP) yield and standard quality. Bio-insecticide is an effort to fulfill the standard based on GACP. Indonesian’s biodiversity have many potential raw materials of bio-insecticides, such as Tithonia diversifolia. The most common pest in the medicinal plants is Aleurodicus dugesii (giant whiteflies), this insect belong to Hemiptera ordo and Aleyrodidae family. The research was conducted to determine the antifeedant and anti-oviposition activity of Tithonia bio-insecticide against giant whitefly on Coleus species. The experimental design was completely randomized design (CRD) with five treatments of Tithonia leaves extract consentrations. Those consentrations were 0, 4, 2, 1, and 0,5 mg L-1. The treatments were tested by using a no-choice test with three replications. The extract of Tithonia leaves was prepared by infundation method by using water solvent. Results showed that extracts of Tithonia with the smallest concentration (0,5 mg L-1) has an active role as an anti-oviposition and antifeedant on giant whiteflies.